Inhibition of 5’-methylthioadenosine metabolism in the Yang cycle alters polyamine levels, and impairs seedling growth and reproduction in Arabidopsis - Bürstenbinder, Katharina; Wirtz, Markus; Hell, Rüdiger (The plant journal, 2010)
The methionine or Yang cycle recycles Met from 5’-methylthioadenosine (MTA) which is produced from S-adenosyl-L-methionine (SAM) as a by-product of ethylene, polyamines, and nicotianamine (NA) synthesis. MTA nucleosidase is encoded by two genes in Arabidopsis thaliana, MTN1 and MTN2. Analysis of T-DNA insertion mutants and of wt revealed that MTN1 provides approximately 80% of the total MTN activity. Severe knock down of MTN enzyme activity in the mtn1-1 and mtn1-2 allelic lines resulted in accumulation of SAM/dSAM (decarboxylated SAM) and of MTA in seedlings grown on MTA as sulfur source. While ethylene and NA synthesis were not altered in mtn1-1 and mtn1-2 seedlings grown on MTA, putrescine and spermine were elevated. By contrast, mtn2-1 and mtn2-2 seedlings with near wt enzyme activity had wt levels of SAM/dSAM, MTA, and polyamines. In addition to the metabolic phenotypes, mtn1-1 and mtn1-2 seedlings were growth retarded, while seedlings of wt, mtn2-1, and mtn2-2 showed normal growth on 500 μm MTA. The double knock down mutant mtn1-1/mtn2-1 was sterile. In conclusion, the data presented identify MTA as a crucial metabolite that acts as a regulatory link between the Yang cycle and polyamine biosynthesis and identifies MTA nucleosidase as a crucial enzyme of the Yang cycle.